2020
DOI: 10.1002/ccd.28947
|View full text |Cite
|
Sign up to set email alerts
|

SCAI guidelines on device selection in Aorto‐Iliac arterial interventions

Abstract: Aorto-iliac (Ao-I) disease is quite prevalent and leads to significant limitation in functional status and quality of life. Advances in endovascular therapy (EVT) techniques in the last 25 years, low risk of periprocedural complications and excellent long-term patency have made it possible to treat most symptomatic patients with Ao-I disease using an endovascular-first rather than a surgical approach in addition to guidelines-directed medical therapy. The approach to intra-procedural assessment of Ao-I lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
0
25
0
3
Order By: Relevance
“…Clinical data suggest that EVT in the management of aortoiliac PAD has continued to improve during the last few decades, and development in medical devices has been instrumental in improving the efficacy of the endovascular therapies. [3][4][5][6] Primary stent implantation has significant benefits over angioplasty-based procedures in the early days following the medical intervention. 2 The application of covered stent demonstrated patency benefit over the traditional bare-metal stent (BMS)-based interventions in complex cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical data suggest that EVT in the management of aortoiliac PAD has continued to improve during the last few decades, and development in medical devices has been instrumental in improving the efficacy of the endovascular therapies. [3][4][5][6] Primary stent implantation has significant benefits over angioplasty-based procedures in the early days following the medical intervention. 2 The application of covered stent demonstrated patency benefit over the traditional bare-metal stent (BMS)-based interventions in complex cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A guideline for these stents has been recently reported based on the comprehensive, systematic review and analysis of the scientific evidence, as well as device-specific unbiased recommendations for aortoiliac EVT. 6 The covered stents comprise a metallic scaffold lined with polytetrafluoroethylene or Dacron material. Covered stents are commonly used in the treatment of calcified or ectatic common iliac vessels, where they may provide a safety margin to compensate for the weakness of the BES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that the primary patency after aortoiliac stenting was comparable to extra-anatomical aortoiliac bypass therapy, whereas primary assisted patency or secondary patency was comparable to anatomical aortoiliac bypass therapy 21) . Recently, covered stent has been more widely applied to complex aortoiliac lesions and is expected to improve long-term outcomes 54) .…”
Section: Revascularization For Btk Lesionsmentioning
confidence: 99%
“…SCAI has a long history of prioritizing quality initiatives regarding best practices and the appropriate use criteria in peripheral vascular interventions (PVI) 14 . The society has provided several consensus guidelines (class of recommendation and level of evidence) for device selection in specific clinical or anatomic subsets, based on comparative device safety and effectiveness data 15,16 . However, recent studies continue to show marked heterogeneity of treatment practices in real world settings, both when performed in hospital or at an ASC 17 .…”
Section: Peripheral: Understanding the Value Assessment Of Peripheral Technologies In Acute And Chronic Infrainguinal Interventionsmentioning
confidence: 99%